THE EFFECTIVENESS OF THE LOGOTHERAPY COUNSELING MODEL DEVELOPMENT TO IMPROVE LOW SELF-ESTEEM OF WOMEN VICTIMS OF TRAFFICKING - Engel, Jacob Daan; Yusuf, Samsu (UPI Press, 2013)
The research aimed to produce an effective developmental model of logotherapy counseling toimprove the low self-esteem of women victims of traffi cking. The research employed descriptiveanalyticalmethod, using quasi-experiment because it aimed to describe, analyze, and test theeffectiveness of logotherapy counseling model. The activities of the research consisted of aseries of model validity test, namely model rationality test, model practicability test, limitedtest and fi eld test; hence, the research used research and development, participatory approach,and a mix of qualitative and quantitative research. The techniques of data collection used wereinterview, questionnaire, and observation. The results of the research demonstrated that the useof logotherapy counseling as an intervention program for the experimental group was moreeffective and had given better results in the dynamics of behavior changes among women victimsof traffi cking. The effectiveness was also proven by the results of observation and interview,showing positive values in the dynamics of victims’ behavior changes. Logotherapy counselingmodel has its strengths in self-exploration, self-acceptance, dissociation, self-transcendence,attitudinal values, and self-awareness, which are integrated with self-potential, self-activity andself-evaluation, so that the model can trigger positive changes among the women victims oftraffi cking. Therefore, there should be a training manual of logotherapy counseling model forsocial workers in order to improve both conceptual and empirical aspects of treatment, wherethe former focuses on material comprehension, problem and skill development; and the latteron technique, counseling strategy and approach.Keywords: Effectiveness, Model Development, Logotherapy Counseling, Low Self- Esteem,Women Victims of Trafficking